2009
DOI: 10.1371/journal.pone.0007819
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Human Choline Kinase α and β Enzymes in Lipid Metabolism: Implications in Cancer Onset and Treatment

Abstract: BackgroundThe Kennedy pathway generates phosphocoline and phosphoethanolamine through its two branches. Choline Kinase (ChoK) is the first enzyme of the Kennedy branch of synthesis of phosphocholine, the major component of the plasma membrane. ChoK family of proteins is composed by ChoKα and ChoKβ isoforms, the first one with two different variants of splicing. Recently ChoKα has been implicated in the carcinogenic process, since it is over-expressed in a variety of human cancers. However, no evidence for a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 54 publications
9
83
0
Order By: Relevance
“…Although our approach illustrates tissue heterogeneity, the use of microdissection techniques and larger samples size may reduce the variation observed in the presented results. In a number of studies, CHKA has been shown to mediate cellular proliferation, transformation, and carcinogenesis, and mediation of this target using siRNA and smallmolecule inhibitors suggests inhibition of tumor growth (11,16,18,40,41). As indicated, we further observed in clinical samples and endometrial cancer cell lines, a significant increase in the mRNA expression of enzymes of the phosphatidylcholine deacylation pathway; GPCPD1, LYPLA1, and LYPLA2.…”
Section: Discussionsupporting
confidence: 61%
“…Although our approach illustrates tissue heterogeneity, the use of microdissection techniques and larger samples size may reduce the variation observed in the presented results. In a number of studies, CHKA has been shown to mediate cellular proliferation, transformation, and carcinogenesis, and mediation of this target using siRNA and smallmolecule inhibitors suggests inhibition of tumor growth (11,16,18,40,41). As indicated, we further observed in clinical samples and endometrial cancer cell lines, a significant increase in the mRNA expression of enzymes of the phosphatidylcholine deacylation pathway; GPCPD1, LYPLA1, and LYPLA2.…”
Section: Discussionsupporting
confidence: 61%
“…AEA-generated (25), most of the studies on AEA uptake have been performed using cancer cell lines that have been shown to possess a high activity of the PL biosynthesis pathway due their rapid and unlimited proliferation rate (18). In fact, choline kinase has been reported to be overexpressed in many cancer types, where it promotes proliferation (79). In the present study, we show that the human U937 monocyte leukemia cells retain the vast majority of the AEA-derived [ 3 H]ethanolamine in PLs within 5 min due to the high rate of PL biosynthesis in this cell line (80).…”
Section: Distinct Incorporation Of [ 3 H]ethanolamine and [ 3 H]glycementioning
confidence: 99%
“…This suggests that the synthesis of phosphocholine is inhibited due to reduced choline transport and/or phosphorylation. CK ␣ is the major isoform expressed in MCF7 cells and is overexpressed in many types of cancer ( 48 ). However, total CK activity in the cytosolic fractions from control and camptothecin-treated MCF7 and MCF7-C3 cells was similar ( Fig.…”
Section: Inhibition Of Choline Uptake In Camptothecin-treated Cellsmentioning
confidence: 89%